PENGARUH FASILITAS DAN LOKASI TERHADAP KEPUTUSAN BERKUNJUNG KE WISATA AIR TERJUN DLUNDUNG MOJOKERTO - Rahayu; Yahya; Hartono (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2021)
This research examines influence of facilities and locations on the decision to visit the dlundung waterfall Mojokerto, the first problem studied was the influence of facilities on visiting the dlundung waterfall Mojokerto , the second problem was the influence of the location on visiting the dlundung waterfall Mojokerto and the third problem about the influence facilities and location of the decision to visit the dlundung waterfall Mojokerto. This study aims to determine the extent of the influence of facilities (X1) and location (X2) on the decision to visit the tourism of dlundung waterfall Mojokerto. the method used in this study is a non probability sampling method by means of incidental sampling. The sample used in this study was 100 tourists who visited the tour of the dlundung waterfall . The analytical method used is multiple linear analysis. This type of research is quantitative. The data obtained are primary data from the respondent's answers to the questionnaire distributed. The results of the research show that the facility variable (X1) has no effect on the decision to visit the dlundung reservoir, as evidenced by the t test where tcount <ttable is 0.384 <1.661, and the probability value is greater than 0.05 which is 0.702> 0.05 . Whereas the location variable (X2) influences the decision to visit the dlundung Mojokerto reservoir, as evidenced by the t test where t count> t table is (5,999> 1,661). While the significant probability value is greater than 0.05, which is 0,000> 0.05. and the results of simultaneous test facilities and location variables have a low effect of 29.4% while the remaining 70.6% is explained by variables not examined for the decision to visit the dlundung waterfall Mojokerto.